An M12(L1)12(L2)12 Cantellated Tetrahedron: A Case Study on Mixed‐Ligand Self‐Assembly1. (7th October 2014) - Sun, Qing‐Fu; Sato, Sota; Fujita, Makoto
Abstract In the self‐assembly of PdII ions and two different, but similarly shaped, ligands (1 and 2), neither random mixing nor self‐sorting of the two ligands into two unmixed structures was observed. Instead a mixed, yet sorted, Pd12(1)12(2)12 cantellated tetrahedron (and its pseudoisomer) was selectively formed, thus revealing a fine example of intramolecular self‐sorting. A case study showed that a homothetic ratio of >2 is necessary to observe cantellated tetrahedra.